You are on page 1of 2


1. Derive Gibbs Helmholtz equation.
Consider the following relations,
G = HTS (Gibbs free energy)
H = E + PV (enthalpy)
G = E + PV TS
For infinitesimal change,
dG = dE + P dV + V dP T dS S dT .(1)
But according to first and second law of thermodynamics,
dE = dq P dV (first law )
dq = T dS (second law)
Therefore, dE = Tds Pd V (2)
Substituting equation 2 in 1 we get,
dG = TdS P dV + P dV + V dPT dSS dT
dG = V dPS dT ..(3)
At constant pressure dP = 0, equation (3) becomes
dG = --S dT (4)

= --S .(5)

Substituting equation (5) in G = H TS, we get
G = H +

(or) G ---T = H
This is one form of the Gibbs Helmholtz equation.

For any two states of the system the equation (4) may be written as,
dG1 = ---S1dT (initial state)
dG2 = --S2dT (final state)
To get the change
dG2dG1 = --S2dT(--S1dT)
d(G2G1) = -- ( S2S1)dT
At constant pressure the equation (7) becomes

= -- S
But, according to definition of free energy

S =

Substituting equation (9) in 8, we get

= T

= H + T

Similarly A = E + T

This is another form of Gibbs-Helmholtz equation
2. Derive Clausius Clapeyron Equation.
Consider a system consisting of only 1 mole of a substance existing in two phases A and B. The free energies of the substance in two
phases A and B be GA and GB. Let the temperature and pressure of the system be T and P respectively.The system is in equilibrium,
so there is no change in free energy.i.e.,
If the temperature of the system be raised to T + dT, the pressure becomes P + dP and the free energies become GA + dGA and GB +
dGB respectively. Then the equation (1) becomes
GA + dGA = GB + dGB
We know that
G = H TS (Gibbs free energy)
Therefore H = E + PV (enthalpy)
G = E + PVTS
dG = dE + P dV + VdP